Effect of relative humidity on the performance of five cost-effective PM sensors. Issue 8 (22nd June 2021) - Wang, Peng; Xu, Feng; Gui, Huaqiao; Wang, Huanqin; Chen, Da-Ren
Abstract: In this work, the effect of relative humidity, RH, on the readouts of five light-scattering-based PM sensors were investigated by using particles composed of different hydroscopic materials and comparing the readouts with those measured by Tapered Element Oscillating Microbalance (TEOM). It was found the RH has various effects on the readouts of PM sensors, highly depending on the hydroscopic property of particles. Negligible RH effect on the PM sensors' readouts was observed for hydrophobic particles while significant increase in the readouts was observed for hydroscopic particles at the RH setting higher than the deliquescence relative humidity, DRH, of particle materials. For particles in the binary components, the effect of the mixture deliquescence on the sensor readouts depends on the hygroscopicity of composite materials (e.g., NaCl + Glucose; NaCl + OA; NaCl + K2 SO4 ). In the case of NaCl + OA, the water uptake of resultant NaCl + OA particles is less than that of pure NaCl and OA (because of the possible formation of less hygroscopic di-sodium oxalate, Na2 C2 O4, in particles). The readouts of PM sensors were also influenced by the mixing status of particles, i.e., internally vs. externally mixed. The correlation slopes for different PM sensors were compared. More, the sampling misalignment was found affecting the readouts of some PM sensors. It is thus suggested to calibrate PM sensors using field particles under the application environments for getting PM data in good quality (assuming that the seasonal change of field RH, and the size distribution and composition of field particles is minor). Copyright © 2021 American Association for Aerosol Research